Physicochemical property and microbial community characteristics of the casing soil for cultivating Oudemansiella raphanipes - Liu, Jinjia; Qin, Zhongyu; Wu, Jinqiang; Su, Jiao; Feng, Pengcheng; Su, Wenting (Frontiers in Microbiology, 2024)
BackgroundCasing soil is critical for the cultivation process of Oudemansiella raphanipes and promotes the formation of mushroom fruiting bodies. Therefore, reliable casing soil indicators are crucial for obtaining high yields of high-quality mushrooms.MethodsIn this study, soil enzyme activity, physicochemical properties, and microorganisms at five cultivation stages [namely casing (A1), mycelial (A2), primordial (A3), fruiting (A4), and harvesting (A5)] of O. raphanipes cultivation were evaluated in casing soils.ResultsThe results indicated that sucrase and catalase activities were significantly increased with increasing cultivation time (p < 0.01), and the activities peaked [16.67 and 0.25 g/(g·h), respectively] at A4. Urease activity peaked [1.56 g/(g·h)] at A1, and it decreased gradually (p < 0.01). Polyphenol oxidase activity was significantly higher at A2 [0.95 g/(g·h)] than at the other stages and was significantly lower at A1 [0.06 g/(g·h)]. Soil pH peaked at A1 (8.20) and decreased gradually (p = 0.003). Soil total organic carbon content increased significantly with increasing cultivation time (p < 0.001) and was the highest at A5 (8.40 g/kg). The available phosphorus at A1 (0.40 g/kg) was significantly higher than those at the other stages (p = 0.004), and the available nitrogen at A1 (0.28 g/kg) and A3 (0.26 g/kg) was significantly higher than those at the other stages (p < 0.001). The number and diversity of bacteria and fungi in soil increased gradually, and nine bacterial and four fungal genera were identified.ConclusionThis study offers soil characteristic and microbial community data for O. raphanipes casing soil at different cultivation stages, which could facilitate sustainable cultivation of O. raphanipes and reduction of live contaminants.